Analisis Framing Kompas. Com Dan Tempo.Co Pada Pemberitaan All Eyes On Papua Periode 31 Mei-22 Juni 2024 - Resti Rahmawati; Ilham Gemiharto; Samson CMS (KOMVERSAL, 2025)
The All Eyes on Papua movement has shocked the Indonesian people, because it turns out that there is an important problem behind the movement. This problem is the seizure of the customary forests of the Awyu and Moi tribes in Papua which will be turned into oil palm plantations. This research analyzes the framing of Kompas.com and Tempo.co online media regarding the issue of “All Eyes on Papua” in the period from 31 May to 22 June 2024. Using a qualitative method, this research explores how the two media framed the issue through analyzing relevant articles. The results show that Kompas.com emphasized humanitarian aspects and environmental impacts, while Tempo.co focused more on criticism of government policies and protection of indigenous peoples' rights. Kompas.com defined All Eyes on Papua, as an environmental and development issue, while Tempo.co tends to see it as a political and humanitarian issue. Kompas.com sees the cause of this problem as the government's lack of attention to balance and the rights of indigenous peoples, while Temp.co considers that this happened because the government issued a feasibility permit without FPIC. The moral consideration given by Kompas.com is that the government should respect the rights of the community and return their land, while Tempo.co considers that the government does not respect the rights of indigenous peoples. The problem solving offered by Kompas.com is that the government involves indigenous peoples and is processing the return of customary land, while Tempo.co that the government should change policies that can protect customary forests. This research recommends that the media be more diverse in presenting perspectives and providing space for indigenous voices in the news.